СONSCIOUS SELF-REGULATION AND SUBJECTIVE WELL-BEING IN EARLY ADOLESCENCE: A LONGITUDINAL STUDY - Fomina, T.G.; Morosanova, V.I. (Modern Psychology, 2019)
The article presents research results on the relationship between conscious self- regulation of the learning activities and subjective well-being of the younger adolescents in the school environment. Diagnostics included assessment of the regulatory processes and intrapersonal-regulatory features (“Self-regulation of the Learning Activity Questionnaire”, Morosanova, 2015) and certain aspects of the students’ life satisfaction (“Multidimensional Children’s Life Satisfaction Scale”, Sytchev et al., 2018). The sample consisted of the 4-6 graders of the Russian schools (N=515). According to regression analysis results, the General level of self-regulation and particular individual regulatory characteristics turned to be significant predictors of the students’ subjective well-being. Their specificity is described for the students of 4, 5, 6 grades. Cross-longitudinal analysis allowed to establish that conscious self-regulation of the learning activity is a significant predictor of the subjective well-being stability during the students’ transition from the primary to the middle school, so it serves as a reliable predictor of the schoolchildren’ well-being in subsequent ages.